Pengaruh Beban Kerja, Stress Kerja, Dan Work-Life Balance Terhadap Kinerja Karyawan Generasi Z Di DKI Jakarta - Alya Salsabila; Dewi Kurniawati (Universitas Pakuan, 2026)
The Effect of Workload, Job Stress, and Work-Life Balance on the Performance of Generation Z Employees in DKI Jakarta This study is motivated by the growing demand for employee productivity in urban workplaces, particularly among Generation Z employees who face dynamic work demands, psychological pressure, and the need to maintain work-life balance. Generation Z employees are generally adaptive to technology, yet they also place strong emphasis on flexibility, mental well-being, and personal life balance. This study aims to analyze the effect of workload, job stress, and work-life balance on the performance of Generation Z employees in DKI Jakarta. A quantitative approach with descriptive and causal-associative methods was employed. Data were collected through questionnaires distributed to 113 Generation Z employees working in DKI Jakarta. The data were analyzed using validity and reliability tests, classical assumption tests, multiple linear regression, partial tests, simultaneous tests, and coefficient of determination with SPSS 27. The findings indicate that workload does not have a significant partial effect on employee performance, while job stress has a significant effect on employee performance. Furthermore, work-life balance has a positive and significant effect on employee performance. Simultaneously, workload, job stress, and work-life balance significantly affect employee performance, with an Adjusted R Square value of 0.791, indicating that the three variables explain 79.1% of the variance in employee performance. These findings imply that organizations should manage job stress effectively, strengthen policies that support work-life balance, and regulate workload proportionally to improve the sustainable performance of Generation Z employees in DKI Jakarta.